If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3d + -8) = 1.3(-6 + -9d) Reorder the terms: -2(-8 + 3d) = 1.3(-6 + -9d) (-8 * -2 + 3d * -2) = 1.3(-6 + -9d) (16 + -6d) = 1.3(-6 + -9d) 16 + -6d = (-6 * 1.3 + -9d * 1.3) 16 + -6d = (-7.8 + -11.7d) Solving 16 + -6d = -7.8 + -11.7d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '11.7d' to each side of the equation. 16 + -6d + 11.7d = -7.8 + -11.7d + 11.7d Combine like terms: -6d + 11.7d = 5.7d 16 + 5.7d = -7.8 + -11.7d + 11.7d Combine like terms: -11.7d + 11.7d = 0.0 16 + 5.7d = -7.8 + 0.0 16 + 5.7d = -7.8 Add '-16' to each side of the equation. 16 + -16 + 5.7d = -7.8 + -16 Combine like terms: 16 + -16 = 0 0 + 5.7d = -7.8 + -16 5.7d = -7.8 + -16 Combine like terms: -7.8 + -16 = -23.8 5.7d = -23.8 Divide each side by '5.7'. d = -4.175438596 Simplifying d = -4.175438596
| -3j^2=-9j | | 4/5x=31/5 | | kx^2-5kx-24k= | | -3+(4-7x)=1.3(6+3x) | | 6t^2-t-7=0 | | 5x^2-45x+90= | | f^2+42-13f= | | -5-(9y+7)-y=1.4(4-12y) | | -5x+8-2x=-27 | | 5m-1(6m+9)=11 | | 5u^2=9u | | 60+x^2-17x= | | -18=k+54 | | 0=10w-10 | | 4-(-5+x)=-9 | | 3(2z-4)-4z=-1.5(20z+10) | | 4=5x+6x+4 | | -3q^2+6q-3=0 | | -56+n^2+n= | | 8(x-3)=48 | | 7=38-3 | | 17-2v=41 | | 12-2(n-3)=-2 | | -3(2m-1)+4m=-3m+11 | | -2s^2+5s-2=0 | | 3(x-2)=6x-12 | | (7x)=(4x^9) | | 3x/3=9 | | 3h-5(h+3)-h=3-2(3h+4) | | 3h-5(h+3)-h=3-2(3h+4) | | 5=13n-21 | | 2-2(2x+7)+7x=2x+3(4-9x) |